ความหลากหลายทางเทคโนโลยีวัฒนธรรมการสื่อสารในยุคปัจจุบัน - อุทยานิน, บุญเทิด (Journal of Human and Society, Sisaket Rajabhat University, 2022)
บทความนี้มีวัตถุประสงค์เพื่อศึกษาความหลากหลายทางเทคโนโลยีวัฒนธรรมการสื่อสารในยุคปัจจุบัน โดยศึกษาในพื้นที่ของกลุ่มชาติพันธุ์เมี่ยนและคนภูเขาใน อนุภูมิภาคลุ่มน้ำแม่โขง ใช้ระเบียบวิธีเชิงคุณภาพ รวบรวมข้อมูลจากแหล่งข้อมูล ทุติยภูมิ ทบทวนวรรณกรรมที่เกี่ยวข้อง สนทนาอย่างไม่เป็นทางการ และสัมภาษณ์เชิงลึกกลุ่มผู้ให้ข้อมูลหลัก ได้แก่ ผู้ที่มีประสบการณ์ใช้เทคโนโลยีการสื่อสารจำนวนไม่น้อยกว่า 10 คน แล้วสรุปใจความสำคัญเกี่ยวกับความหลากหลายทางเทคโนโลยีวัฒนธรรมการสื่อสารในยุคปัจจุบัน ผลการวิจัย พบว่ามีประเด็นที่น่าสนใจ ดังนี้ 1. พัฒนาการของเทคโนโลยีการสื่อสารมนุษย์ได้พัฒนาการสื่อสารจาก อดีตกาล โดยมีหลักฐานทางโบราณคดีบางอย่างที่สื่อสารเพื่อสื่อความหมายมาเรื่อย ๆ จนถึงยุคที่เทคโนโลยีการสื่อสารทั้งข้อความ อินเตอร์เน็ต ภาพนิ่ง วีดีโอและอื่น ๆ ที่รวดเร็วภายในระยะเวลาสั้นๆ ในปัจจุบัน 2. องค์ประกอบของเทคโนโลยีการสื่อสาร ที่สำคัญมี 3 ประการ ได้แก่ ระบบประมวลผล ระบบสื่อสารโทรคมนาคม และการจัดการข้อมูล 3. วัตถุประสงค์ของการสื่อสาร คือ เพื่อควบคุม เพื่อรวบรวมข้อมูล เพื่อการสังคม และเพื่อลดความตึงเครียด 4. ความสำคัญของการสื่อสาร ได้แก่ ก่อให้เกิดการประสานสัมพันธ์กันระหว่างบุคคลและสังคม เป็นปัจจัยสำคัญในการดำรงชีวิตของมนุษย์ทุกเพศ ทุกวัย และเป็นปัจจัยสำคัญในการพัฒนาความเจริญก้าวหน้าทั้งตัวบุคคลและสังคม 5. ลักษณะของการสื่อสาร มี 3 ประการ ดังนี้คือ เป็นเรื่องที่เกี่ยวกับการก่อให้เกิดความหมายให้กับผู้ฟัง เป็นเรื่องเกี่ยวข้องกับการส่งข้อมูลจากที่หนึ่งไปยังอีกที่หนึ่ง และเป็นเรื่องเกี่ยวข้องกับการกระตุ้นเตือนหรือการชักนำให้บุคคลคล้อยตามหรือเห็นด้วยกับข้อมูลนั้น ๆ This article has an objective to study the diversity of cultural technology on communcation in the present day by studying in the areas of Mien ethnic group and hill tribe people in The Greater Mekong Subregion. By using a qualitative methods to collect data from secondary sources by reviewing related literature, informal conversations and in-depth interviews with 10 key informants who had experiences on using communication technologies. And conclude the important information about diversity in communication cultural technology in present day. The results of this research found out the interesting issues as follows: 1.The development of human communication technology has gradually developed from the past with some archaeological evidences revealing that communication has been used to convey meaning and developed through time until the era of communication technology, including instant messaging, images, videos and others in the present day. 2. There were 3 important communication technology elements, which are, processing system, telecommunication system, and information management. 3.The purpose of communication were to control, to collect and gather information, to socialize and to reduce tension. 4.The importance of communication was to created a coordination between people and society. it is an important factor in human life of all sex and all ages. And it is also an important factor in the development of both individuals and society. 5.There were 3 characteristics of communication as follows: It was about creating meaning for the listener. It was related to sending information from one place to another, a was related to urging or inducing people to conform to each other or agree with the information.